Knowledge, attitude and practice of osteoporosis prevention among female adults community in Penambang, Kelantan - Anuar, Muhammad Tarmizi (Universiti Sains Malaysia, 2014)
Osteoporosis is a serious public health issues, affecting up to 1 in 2 women over the age 50 years old. The Malaysian generally are not serious to take care about osteoporosis, that's why it is important to enhance and promote good bone health. This study is a cross-sectional designs, descriptive study. These study was carried out to identify the relationship between knowledge, attitude and practice of osteoporosis prevention among female adults in Kampung Bunga Mas community, Penambang, Kota Bharu, Kelantan. Approximately 90 of females adults ages ranged from 40 until 60 years old have completed questionnaires by purposive sampling method for female adults that meet the inclusion criteria. Data was collected by using Oteoporosis Knowledge Test (OKT), attitude toward osteoporosis and practice toward osteoporosis. Data was statistically analyzed by using the software package SPSS version 21. The statistical significance was considered at p-value <0.05. Descriptive statistic were used to determine the prevalence of osteoporosis. Meanwhile, the independent t-test and One Way Anova test were used to describe the association between selected socio-demographic data (age and level of education) with knowledge, attitude and practice of osteoporosis prevention among respondents. There was significant association between age and practice of prevention osteoporosis since the p-value was 0.031 (p<0.05). In addition, the p-value of One Way Anova test for level of education and knowledge score was 0.001 (p<0.05) and the result shown that there was significant association between level of education and knowledge of osteoporosis prevention among respondents. The relationship between knowledge, attitude and practice of osteoporosis prevention was tested by using Pearson's correlation. The p-value of knowledge and attitude was 0.125 (r=0.163), p-value of knowledge and practice was 0. 734 (r=0.036), and p-value of attitude and practice was 0.951 (r=0.007). From the result, it was revealed that there were no relationship between knowledge, attitude and practice of osteoporosis prevention and no direct correlation between these variables.